Alkyl-chain-separated triphenybenzene - carbazole conjugates and their derived polymers: candidates for sensory, electrical and optical materials - Kaleeswaran, D.; Vishnoi, Pratap; Kumar, Subramani; Chithiravel, Sundaresan; Walawalkar, Mrinalini G.; Krishnamoorthy, Kothandam; Murugavel, Ramaswamy (Chemistry Select, 2016)
Four new triphenylbenzene based carbazoles (THPBCz4, THPBCz6, THPBCz8 and THPBCz10) and polycarbazoles (polyTHPBCz4, polyTHPBCz6, polyTHPBCz8 and polyTHPBCz10), have been synthesized. Photoluminescence spectra of the monomers in dichloromethane exhibit two intense bands at 353 and 369 nm. Two additional bands (410 and 435 nm) are also observed due to intermolecular interactions. These bands are more intense in the case of thin films, indicating stronger pp stacking interactions in the solid state. Due to the extended p-conjugation, the polycarbazoles display two main emission bands (495 and 520 nm) which are red shifted as compared to the monocarbazoles. Due to the presence of emissive platforms such as triarylbenzene and carbazole, both monomers and polymers, function as efficient sensors for the detection of polynitroaromatic analytes (PA, DNT, rho-DNB and m-DNB). The electrochemically polymerized carbazole derivatives showed maximum capacitance of 41 F/g for polyTHPBCz6. The SCLC measurement reveals a maximum mobility of 6 x 10(-6) cm(2)/Vs for polyTHPBCz4 that showed better packing due to flexible alkyl chains that connect the conjugated moieties.